2014
DOI: 10.21273/hortsci.49.6.769
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Preferences for Longevity Information and Guarantees on Cut Flower Arrangements

Abstract: Choice experiments were conducted to explore the market potential or value added when using longevity information and guarantees on cut flower arrangements in the retail setting. The objective of our study was to determine consumer preferences and willingness to pay for different vase life longevities and guarantees on cut flower arrangements. The choice experiment data were collected using online surveys with 525 U.S. consumers in July 2011. The choice experiment scenarios included single species or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 23 publications
1
25
1
Order By: Relevance
“…A typical flower purchaser tends to be an older than 40 years old, Caucasian, married female with high education and income levels, and with more earners but fewer members in the household. Part of the profile is consistent with previous findings, including younger consumers having decreased awareness and interest in floral products compared with older consumers (Rihn et al, 2011), whereas higher income (Yue and Behe, 2010), higher education level (Yue and Hall, 2010), and smaller family size (Rihn et al, 2014) were positive determinants of flower expenditures.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…A typical flower purchaser tends to be an older than 40 years old, Caucasian, married female with high education and income levels, and with more earners but fewer members in the household. Part of the profile is consistent with previous findings, including younger consumers having decreased awareness and interest in floral products compared with older consumers (Rihn et al, 2011), whereas higher income (Yue and Behe, 2010), higher education level (Yue and Hall, 2010), and smaller family size (Rihn et al, 2014) were positive determinants of flower expenditures.…”
Section: Resultssupporting
confidence: 89%
“…Other reports have shown that education and income level affect consumers' choice of flower categories and expenditure level on flowers (Yue and Behe, 2008). Lastly, a decrease in family size (Behe et al, 1999) and being married (Rihn et al, 2014) are positively associated with floral consumption.…”
mentioning
confidence: 89%
“…The postharvest disorders in cut rose flowers are a major limitation in their ornamental value (Rihn et al, 2014). In order to prolong vase life of cut flowers, many previous studies have been conducted to reduce ethylene damage using various ethylene inhibitors, such as nitric oxide, silver thiosulfate (STS), and 1-methylcyclopropene (1-MCP), which repressed the transcript levels of ethylene biosynthesis and receptor genes (Chamani et al, 2005;Liao et al, 2013;Ichimura and Niki, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the attribute appearance reflects the ultimate purpose of an ornamental flower, namely, beautification, it is noteworthy that the preference share for appearance is not expressed even more dominantly. In contrast, the preferences for the freshness guarantee are not surprising; consumers seem to have an interest in ornamental products with a longer vase life, as earlier studies have also shown (Rihn et al, 2014). Studies on other agricultural products, such as meat or fresh produce, also show that a long shelf live is a desired product attribute for consumers (Varela et al, 2005).…”
Section: Educationmentioning
confidence: 97%
“…Besides personal use, cut flowers Previous analyses of consumer demand for flower attributes Prior studies of consumer behaviour explore the importance of particular product attributes when choosing flowers and explore how demographic factors may be related to these preferences. Attributes found to be influencing consumer's choice are flower appearance (Hudson and Griffin, 2004;Yue and Behe, 2008), scent (Behe and Wolnick, 1991;Behe et al, 1992), packaging (Hall et al, 2010), country of origin (Hoffmann, 2000;Van Loo et al, 2011), longevity (Rihn et al, 2014), flower certification (Michaud et al, 2013) and price (Yue, Hurley and Anderson, 2011;Michaud et al, 2013). However, while each of these attributes is important to some segment of consumers, the relative levels of importance amongst these attributes are expected to vary across individuals.…”
Section: Introductionmentioning
confidence: 99%